Diagnosis of Toxocara spp. eggs from soil in parks and public squares of the Barquisimeto city, Lara state, Venezuela. (Gaceta de Ciencias Veterinarias, 2015)
Humans, and especially children, can be infected with several nematodes which affect dogs and cats (Toxocara spp., Ancylostoma spp., among others). Human infection with Toxocara spp. is acquired by contact with larvae fertile eggs of this parasite, which persist as infectious eggs for years in moisture soil and warm temperatures; transmission to humans is by oral route through food, water or hands contaminated with soil and Toxocara spp. eggs. Parks and public squares are places for people recreation, but it is frequently observed the presence of canines and felines which routinely deposit their feces contaminant park’s soils. The aim of this study was the diagnosis of Toxocara spp. larvated eggs from soil samples of public squares and parks of Barquisimeto, Lara state, Venezuela. Recreational sites were selected according to inclusion criteria, and soil samples were collected using the system of the double “V”; samples were analyzed using the Sloss modified technique. For calculations, SPSS 15.0 for Windows was used. The diagnosis of eggs of Toxocara spp. was confirmed in 62.5% of recreational sites investigated, and this finding represents a public health problem and an alert to the exposed population.
Keywords: Toxocara; zoonoses; contaminated soil; dogs; cats